PENGARUH PENDAPATAN RUMAH TANGGA, PENDIDIKAN IBU TERHADAP KEJADIAN STUNTING DI DESA INDRA SAKTI KECAMATAN TAPUNG KABUPATEN KAMPAR - ,Selly Prima Desweni, Adiyan Shiddiqi , Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research is based on the dangers of stunting, and the stunting condition that is still high in Kampar Regency, especially in Tapung District in 2021. Stunting certainly affects the growth and development of a child. Based on these problems, this study aims to 1) analyze the effect of income level on the incidence of stunting in Tapung District, Kampar Regency in 2021. 2) The influence of parental education level on stunting incidence in Tapung District, Kampar Regency in 2021. In this study the author uses quantitative research approach methods. The number of samples used in this study were 55 parents of toddlers who experienced stunting in Indra Sakti Village, Tapung District. Data analysis technique is to use multiple regression model. The results of hypothesis testing indicate that: 1) Education has no significant effect on the incidence of stunting in Indrasakti Village, Tapung District. 2) Income level has a positive and significant influence on the incidence of stunting in Indrasakti Village, Tapung District. Based on the results of the study, several recommendations can be given, namely as follows: 1) The community must be wiser in providing nutritional intake to children, 2) To the government, in order to carry out the stunting eradication program to the maximum, Keywords: Education, Income Level, Stunting.